Pengaruh Kompetensi Pedagogik, Kompetensi Profesional Terhadap Kinerja Pengenalan Lapangan Persekolahan Mahasiswa Pendidikan Akuntansi - Ervina Hardianti; Agung Listiadi (Jurnal Pendidikan Akuntansi (JPAK), 2021)
The study was conducted with the aim of knowing whether there was an effect of pedagogic and professional competence on the performance of accounting students partially or simultaneously. This research is included in causal associative research, which means that this study looks for a causal relationship between variables. The research was conducted on accounting education students at the State University of Surabaya who had implemented PLP with a total population of 245 students. The sample used is simple random sampling, so it is found a sample of 152 students. Data collection techniques using secondary data obtained from student scores. The results of the t test: (1) pedagogical competence affects PLP performance with a significant result of 0.000 (2) professional competence affects PLP performance with a significant result of 0.001. The result of the F test is 22,309 with a significant result of 0,000, this indicates that there is a simultaneous effect of pedagogic and professional competence on the performance of accounting education students at the State University of Surabaya. In addition to the t test and F test, there is an R Square value of 23% which indicates that PLP performance is affected by 23% by the pedagogical and professional competency variables, while 77% is influenced by other factors or variables. From the results of the research conducted, it shows that there is an influence of Pedagogic Competence and Professional Competence on the performance of accounting education students' school field introduction either partially or simultaneously.